Public Perception of Governance, Corruption, and Their Impact on Sustainable Development: Evidence from Butwal, Nepal (Surkhet Journal, 2025)
This study examines public perceptions of governance quality, corruption, and sustainable development in Butwal and surrounding areas of Nepal. Despite transitioning to a democratic system in 1990, Nepal continues to face persistent governance challenges, including systemic corruption, weak institutional accountability, and political instability. Using a structured questionnaire administered to 90 participants, the study employed descriptive analysis, chi square tests, t-tests, and logistic regression to analyze public opinion. While more than half (55.5%) of respondents expressed dissatisfaction with government employees, a slight majority (51.1%) acknowledged timely service delivery. This suggests that factors beyond timeliness—such as transparency, fairness, and staff conduct—significantly influence public satisfaction. Perceptions of infrastructure showed notable improvement: positive assessments of roads and streets increased by 30 percentage points, and hospitals by 25 points, all statistically significant (p < 0.001). Key drivers of corruption included fast service, low public sector salaries, and inadequate reporting mechanisms, with the most severe perceived impacts being stalled development, weakened governance, and increased inequality. Regression analysis indicated that political instability, corruption, and complex legal frameworks significantly increase the likelihood of individuals facing barriers to business or employment. Respondents identified proper investigations, prompt service delivery, and strict legal enforcement as the most effective anti corruption measures. The study concludes that administrative reforms focusing on transparency, simplified legal procedures, and improved staff conduct, coupled with efforts to stabilize politics and combat corruption, are essential for enhancing institutional trust and advancing sustainable development in Nepal.